2018
DOI: 10.14715/cmb/2018.64.11.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hesperetin on inflammatory and oxidative status in trinitrobenzene sulfonic acid-induced experimental colitis model

Abstract: In our study, the effect of hesperetin on inflammatory and oxidative status in trinitrobenzene sulfonic acid (TNBS)-induced experimental colitis model was investigated through different methods. Eighteen Wistar albino male rats were divided in to three groups: Group I (Control, n = 8; 1 ml physiological saline), Group II (Colitis, n = 8; 1 ml TNBS), Group III (Hesperetin, n = 8; 1 ml TNBS and 100 mg/kg hesperetin). Macroscopic and microscopic scores were calculated to determine the damage to the colon at the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…In the current study, the levels of IL-1β and TNF-α increased following silica exposure, and the levels of these inflammatory factors decreased in the 400 mg/kg HSP group on the 28th day. Previous studies have also revealed that HSP can reduce the levels of TNF-α and IL-6, and protect TNBS-induced colitis model via its antioxidation, anti-inflammatory and anti-apoptotic effects (66). It is considered that HSP exhibits a protective effect on many diseases by exerting anti-inflammatory effects (67).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the levels of IL-1β and TNF-α increased following silica exposure, and the levels of these inflammatory factors decreased in the 400 mg/kg HSP group on the 28th day. Previous studies have also revealed that HSP can reduce the levels of TNF-α and IL-6, and protect TNBS-induced colitis model via its antioxidation, anti-inflammatory and anti-apoptotic effects (66). It is considered that HSP exhibits a protective effect on many diseases by exerting anti-inflammatory effects (67).…”
Section: Discussionmentioning
confidence: 99%
“…Hesperidin demonstrated antioxidant activity in rats after an intensive training program, and attenuated the secretion of cytokines by stimulated macrophages [67,68]. The administration of hesperetin has been shown to significantly reduce the levels of myeloperoxidase, malondialdehyde (a marker of lipid peroxidation) and inflammation in experimental models of colitis [69] and hepatic trauma [70]. In a model of rheumatic arthritis induced by Freund's complete adjuvant, hesperidin successfully reversed the signs and symptoms, inflammatory markers and lipid peroxidation [71].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…[ 22,23,37,37,41 ] Interestingly, previous studies on the hesperetin effect on colitis showed similar results for TNF‐α, IL‐6, and NF‐κB. [ 42,43 ]…”
Section: Discussionmentioning
confidence: 72%